Comparison of the Linke turbidity factor in Warsaw and in Belsk - Uscka-Kowalkowska, Joanna; Posyniak, Michał; Markowicz, Krzysztof M.; Podgórski, Jerzy (Bulletin of Geography. Physical Geography Series, 2017)
The article describes the relationship between direct solar radiation in a city (Warsaw) and in its broadly-defined suburban area (Belsk). The analysis covers the days of 1969-2003 when observations were carried out at both sites. The degree of extinction of solar radiation was expressed by means of Linke’s turbidity factor. Its mean annual value on the selected days of the period under consideration was 3.00± 0.10 at Warsaw and 3.00±0.11 at Belsk. Any differences in the atmospheric turbidity between the Warsaw site and Belsk in individual seasons of the year were marginal and within the error margin of Linke’s factor. The period considered was also divided into two sub-periods (1969-1993 and 1994-2003), in which atmospheric turbidity in Warsaw and in Belsk was compared by individual seasons and whole years. At both analysed sites Linke’s atmospheric turbidity factor decreased in 1994-2003, compared to the values for the earlier sub-period (1969-1993). The differences in atmospheric turbidity between the Warsaw site and Belsk are small and often statistically insignificant. The reason for this is, perhaps, the location of the urban measurement site far from the city centre, even though the site was still situated in a typically urban environment.